Labour welfare administration in India - Ram Chandra Prasad Singh (Deep & Deep Publication)
The purpose of the study is to highlight the role of labour welfare in improving the condi tions of worker's life, raising their efficiency and productivity, building up a stable labour force and minimising the chances of conflict between the labour and management.
Keywords: Labour-Welfare